Danau Toba Sebagai Unesco Global Geopark Dalam Perspektif Hukum Lingkungan - Elfira Fitriyani Pakpahan; Mira Handayani; Erwin Mendes; Ayu Mustika (Al-Adl : Jurnal Hukum, 2023)
An area known as a geopark is an area that has three fundamental pillars—conservation, education, and local economic development—and includes significant geological heritage and biodiversity, as well as integrated biodiversity and culture. Development in the fields of culture and tourism is multi-sectoral, interdisciplinary and based on a synergistic system, and is expected to be able to support efforts to educate society, advance civilization, foster national unity and strengthen international friendship. Transport and changes in the cultural and tourism sectors have led to new systems that are more reliable and sustainable. However, the improvements brought about by revolution and reform have not yet reached their full potential. The waters around Lake Toba before it was designated as a UNESCO Global Geopark experienced various disturbances to the preservation of nature due to floating net cages (KJA) animal feed, reduction of land to individual ownership, arbitrariness in the form of logging and waste generated by the community originating from the restaurant business, including oil vessel., which is contaminating the lake water. Toba Government Regulation Number 37 of 2014 concerning Soil and Water Conservation as a legal basis for structuring the Lake Toba Geopark tourism area as a legal umbrella must be holistic, fundamental and partly so that water damage to the surrounding environment can be overcome. This research aimed to analyze the impact of UNESCO's designation of Lake Toba as a Geopark. This research is juridical law research by conducting data collection activities in the form of secondary data. Data analysis used a quantitative descriptive method. The research results show that the government is still trying to maintain the sustainability and beauty of the area by providing education about the ecosystem and realizing Lake Toba as a World Geopark. The government also carries out rehabilitation, reclamation and reforestation of forests to prevent landslides on critical land. It has a Lake Toba Caldera website to implement information on the Toba Caldera area. The existence of Government Regulation Number 37 of 2014 can prevent and preserve the environment around Lake Toba.